PEMBERIAN KREDIT KEPADA WARGA LUAR DESA PAKRAMAN SETEMPAT OLEH LEMBAGA PERKREDITAN DESA (LPD) DESA PAKRAMAN PANGI KECAMATAN DAWAN KABUPATEN KLUNGKUNG - Nova Rianta, I Komang; Eka Wisanjaya, I Gede Pasek (Kertha Semaya : Journal Ilmu Hukum; Vol. 01, No. 10, Oktober 2013, 2013)
This article entitled granting credit to the citizens outside the village of local institutions Ofpakraman village (LPD) Pangi Pakraman Village, Kec. Dawan, Kab. Klungkung. Aiming to find out the procedure for the granting of credit to citizens outside the village of LPD Desa pakraman local by Pakraman Pangi and to know the legal consequences in case of tort by the debtor from outside the village of LPD village Pakraman local Pakraman pangi.The type of research that is used is the type of legal research are emperis.So the procedure or mechanism of granting credit to the citizens outside the village of LPD village pakraman local Pakraman Pangi almost the same procedure of granting credit to villagers and local pakraman in case of the dilakakukan tort by residents outside the village PangiPakraman will repaid through the sale of goods the guarantees shall create any warranty.
Keywords: The Institution Of The Village, Credit, Defaults